INFLUENCE OF IONIZING IRRADIATION ON THE PARAMETERS OF ZN NANOTUBES ARRAYS FOR DESIGN OF FLEXIBLE ELECTRONICS ELEMENTS - D. B. Kadyrzhanov; M. V. Zdorovets; A. L. Kozlovskiy; A. V. Petrov; V. D. Bundyukova; A. E. Shumskaya; E. Yu. Kaniukov (Приборы и методы измерений)
The aim of the study is establishing the possibility of using Zn nanotube arrays as a basis for design compact and lightweight elements of flexible electronics, including operating under influence of ionizing irradiation.The paper presents the results of the synthesis of Zn nanotubes obtained by electrochemical deposition in the pores of polymer matrices and the study of their structural and electrophysical properties after directional modification by ionizing radiation with different doses. Using the methods of scanning electron microscopy, X-ray diffraction and energy dispersive analysis, the structure of nanotubes having a polycrystalline structure and completely consisting of zinc was studied and it was demonstrated that irradiation with Ar8+ ions with a dose from 1 × 109 to 5 × 1011 ion/cm2 and energy 1.75 MeV/nucleon has an effect on the crystal structure of nanotubes.At high doses, localized highly defect zones arise, leading to a critical change in the structure and physical properties of the nanotubes, respectively. It is shown that the consequence of the modification of the crystal structure is a change in the electrical conductivity of nanotubes: at low doses the electrical conductivity increases, but when the threshold value is reached, it sharply decreases. The change in the crystal structure and the corresponding changes in the conductive properties of Zn nanotubes due to irradiation determine the mechanism of ionizing radiation influence on nanomaterials and determine the possibility of using Zn nanotubes arrays as a basis for creating compact and lightweight elements of flexible electronics.